Assessing different irrigation innovations for better climate resilience of olive farming systems in Morocco - Kharrou, Mohamed; Chehbouni, Abdelghani (CGIAR FOCUS Climate Security, 2022)
Drought and water crises jeopardize olive systems (1.1 Mha), a climate adaptation focus of the Green Morocco Plan. This case study with Tensift Basin stakeholders will inform what/where new irrigation innovations could reduce the water footprint of olive systems without economic tradeoffs. Two experiments were established in 2022 near Marrakech (Agdal domaine and on-farm) to test surface and sub-surface drip and deficit irrigation practices. Through hybrid model frameworks, a Climate-Smart Systemic Solutions and Scaling (C4S) yield gap prediction subtool was co-developed to test different irrigation scenarios for olive farms, to know if a combination of irrigation innovation and soil fertilization practices could be a good water and climate resilience option for olive farms. A PhD thesis supervised by Mohammed VI Polytechnic University (UM6P) and Cadi Ayyad University (UCA) began at the end of 2022 on the co-development of appropriate cross-scale fertirrigation guidance resulting from this work.